Ks. Marian Rusecki, Traktat o religii, "Verbinum". Wydawnictwo Księży Werbistów, Warszawa 2007, ss. 620. - Sokołowski, Paweł (Studia Nauk Teologicznych PAN, 2020)
Ks. Marian Rusecki, Traktat o reologii, "Verbinum". Wydawnictwo Księży Werbistów, Warszawa 2007, ss. 620.